Introduction to laser induced breakdown spectroscopy imaging in food: Salt diffusion in meat. (January 2018) - Dixit, Y.; Casado-Gavalda, Maria P.; Cama-Moncunill, R.; Cama-Moncunill, X.; Markiewicz-Keszycka, Maria; Jacoby, Franklyn; Cullen, P.J.; Sullivan, Carl
Abstract: This study illustrates the ability of laser induced breakdown spectroscopy (LIBS) to detect and map minerals in food. A LIBS system was used to spatially collect spectra of beef samples. Samples were brined in a 6% salt solution for 2 h and 24 h along with a control sample. Samples were measured by scanning the cross-section of each sample in a 90 × 90 square grid. Sodium (Na) distribution images with respect to emission peak at 589.05 nm were generated after pre-processing the spectral data which directly corresponds to salt levels. As expected, the control sample showed the lowest Na distribution whereas 2 h brined sample showed distribution along the sample's edges decreasing towards the centre. The 24 h brined sample showed increased diffusion. Overall, results show the ability of LIBS to map salt diffusion in meat via Na LIBS imaging, which could be used to optimize brining conditions. Highlights: LIBS for displaying salt diffusion in beef via sodium (Na) imaging. Pre-processing with baseline correction and normalization. Conversion of spectral data into hypercubes. Image processing with EBImage package in R. Images successfully illustrated salt diffusion process in beef.